Perancangan Hydraulic System Dalam Rangka Mendukung Dies Clamping Pada Mesin Press Seyi SN2-300 di PT Ganding Toolsindo - Edwin Sahrial Solih; Vebriyanti Hayoto; Sanurya Putri Purbaningrum; Fredy Sumasto; Desy Agustin (Fakultas Teknik, 2023)
The problem faced by the PT Ganding Toolsindo company is that it still takes a long time to set the dies on the Seyi SN2-300 Press Machine, this is due to the long process of tightening and releasing the bolts, so it requires a proposed work aid design to shorten the process time for tightening and releasing the bolts. bolt on the die. This research aims to design work aids in the form of a hydraulic system to support die clamping in tightening the dies. The method used in this research is designing tools for the hydraulic system when setting up dies on a press machine. The results obtained by this research are in the form of a hydraulic system design that supports dies clamping during internal press machine setup where this tool can eliminate the operator's work in tightening and releasing bolts during the dies setup process on the Seyi SN2-300 Press Machine at PT Ganding Toolsindo. The design of this hydraulic system is described using CAD software which is based on calculations and dimensions of the dies used in the press machine.